B-cell kinase lyn deficiency in patients with systemic lupus erythematosus - Liossis, S.-N.C.; Solomou, E.E.; Dimopoulos, M.-A.; Panayiotidis, P.; Mavrikakis, M.M.; Sfikakis, P.P. (Journal of Investigative Medicine, 2001)
Background: To better understand the molecular background of B-cell overactivity characterizing systemic lupus erythematosus (SLE), we examined the expression of the CD22 co-receptor and of kinase Lyn, which are involved in signaling inhibitory pathways, in B cells from patients with SLE. Methods: Two-color flow cytometry was used to study the expression of surface antigens on freshly isolated peripheral B cells from patients with SLE, disease-control patients, and healthy volunteers. Intracellular kinases Lyn and Syk were analyzed using Western immunoblots, and differences at the messenger RNA (mRNA) level were evaluated using semi-quantitative polymerase chain reaction (PCR). Results: Expression of B-cell surface CD22 was intact in patients with SLE, but expression of the B-cell kinase Lyn was significantly decreased in resting, as well as in anti-sIgM-stimulated B-cell-enriched cell lysates obtained from 66% of patients with SLE. Lyn deficiency was disease-specific and unrelated to disease activity. Expression of B-cell kinase Syk was similar in all study groups. Semiquantitative PCR revealed that Lyn mRNA was significantly decreased in lupus patients with decreased Lyn protein expression, suggesting that Lyn deficiency may be caused at least in part by defects at the transcription level. Conclusions: Decreased expression of Lyn in some patients with SLE represents a B-cell defect that may enhance our understanding of SLE molecular pathogenesis by providing rational therapeutic targets.
Keywords: B cells; Lyn; signal transduction; Systemic lupus erythematosus; Tyrosine kinases